Development of a method for producing orange smoothie base - Stetsenko, Natalia (My University, 2026)
One of the popular ways to enrich diets with valuable nutrients is to consume smoothies - thick drinks that combine various fruits, berries, plant extracts and other types of raw materials. Such drinks are not only tasty; they are very useful, because they contain significant amounts of vitamins, antioxidants, minerals, dietary fiber, which helps strengthen the immune system and overall health. The technological scheme for obtaining an orange base for a smoothie includes the following operations: washing the fruits, inspecting them, peeling them, squeezing the juice, grinding the pulp, blanching, rubbing, mixing the components, heat treatment, hot aseptic packaging and storage. This method of producing an orange base has a number of advantages. It allows you to reduce the duration of heat treatment of valuable biologically active substances in orange juice. Orange pulp, which contains a significant amount of strong partitions, is processed thermally and mechanically, which allows you to grind them to a homogeneous mass. The orange base has attractive organoleptic properties and valuable biochemical composition. It will combine well with purees of various fruits and berries, extracts of medicinal herbs, which will allow you to create a wide range of health-promoting smoothies. Одним із популярних способів збагачення раціону цінними харчовими речовинами є вживання смузі – густих напоїв, що поєднують різні фрукти, ягоди, рослинні екстракти та інші види сировини. Такі напої не тільки смачні; вони дуже корисні, оскільки містять значну кількість вітамінів, антиоксидантів, мінералів, харчових волокон, що сприяє зміцненню імунної системи та загального стану здоров'я. Технологічна схема отримання апельсинової основи для смузі включає такі операції: миття фруктів, їх огляд, очищення від шкірки, віджимання соку, подрібнення м'якоті, бланшування, розтирання, змішування компонентів, термічну обробку, гаряче асептичне пакування та зберігання. Такий спосіб виробництва апельсинової основи має низку переваг. Він дозволяє скоротити тривалість термічної обробки цінних біологічно активних речовин апельсинового соку. Апельсинова м'якоть, яка містить значну кількість міцних перегородок, обробляється термічно та механічно, що дозволяє подрібнити їх до однорідної маси. Апельсинова основа має привабливі органолептичні властивості та цінний біохімічний склад. Вона добре поєднуватиметься з пюре з різних фруктів та ягід, екстрактами лікарських трав, що дозволить створювати широкий асортимент оздоровчих смузі.
Keywords: смузі; апельсин; здорове харчування; smoothie; health food product; healthy diet; biological value; кафедра технології оздоровчих продуктів